Identification of breast cancer margins using intraoperative near‐infrared imaging. Issue 5 (4th February 2016) - Keating, Jane; Tchou, Julia; Okusanya, Olugbenga; Fisher, Carla; Batiste, Rebecca; Jiang, Jack; Kennedy, Gregory; Nie, Shuming; Singhal, Sunil
Abstract : Background and Objectives: Current methods of intraoperative breast cancer margin assessment are labor intensive, not fully reliable, and time consuming; therefore novel strategies are necessary. We hypothesized that near infrared (NIR) intraoperative molecular imaging using systemic indocyanine green (ICG) would be helpful in discerning tumor margins. Methods: A mammary cancer cell line, 4T1, was used to establish tumors in mouse flanks (n = 60). Tumors were excised 24 hr after intravenous ICG. Assessment of residual tumor in the wound bed was performed using a combination of NIR imaging and traditional method (by visual inspection and palpation) versus traditional method alone. Next we performed a clinical trial to evaluate the role of NIR imaging after systemic ICG for the margin assessment of 12 patients undergoing breast‐conserving surgery. Results: Traditional margin assessment identified 30% of positive margins while NIR imaging identified 90% of positive margins. In our clinical trial, all tumors were detected by NIR imaging and there was fluorescent evidence of residual tumor in the tumor bed in 6 of the 12 patients. None of these patients had positive margins on pathology. Conclusions: Systemic ICG reliably accumulates in breast cancers in murine models as well as human breast cancer. While NIR imaging is helpful for detection of retained tumor margins in our animal model, intraoperative imaging for precise margin detection will need further refinement before clinical value can be obtained. J. Surg. Oncol. 2016;113:508–514 . © 2016 Wiley Periodicals, Inc.